2003
DOI: 10.1021/ja0355574
|View full text |Cite
|
Sign up to set email alerts
|

Active Oxygen Species Generated from Photoexcited Fullerene (C60) as Potential Medicines:  O2-versus1O2

Abstract: To characterize fullerenes (C(60) and C(70)) as photosensitizers in biological systems, the generation of active oxygen species, through energy transfer (singlet oxygen (1)O(2)) and electron transfer (reduced active oxygen radicals such as superoxide anion radical O(2)(-)* and hydroxyl radical *OH), was studied by a combination of methods, including biochemical (DNA-cleavage assay in the presence of various scavengers of active oxygen species), physicochemical (EPR radical trapping and near-infrared spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
514
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(540 citation statements)
references
References 48 publications
17
514
1
5
Order By: Relevance
“…32 In a similar fashion to the tetrapyrrole PS used for photodynamic therapy, 33,34 illumination of fullerenes dissolved in organic solvents in the presence of oxygen leads to the efficient generation of highly reactive singlet oxygen via energy transfer from the excited triplet state of the fullerene.35 However, some recent reports have shown that in polar solvents, especially those containing reducing agents (such as NADH at concentrations found in cells), illumination of various fullerenes will generate different reactive oxygen derivatives, such as superoxide anion. 36 These two pathways (singlet oxygen and superoxide anion) are analogous to the Type II and Type I photochemical mechanisms frequently discussed in PDT with tetrapyrroles. 37 , 38 Fullerenes with their triply degenerate, low lying LUMO are excellent electron acceptors capable of accepting as many as six electrons.…”
Section: Photochemical Mechanismsmentioning
confidence: 89%
See 1 more Smart Citation
“…32 In a similar fashion to the tetrapyrrole PS used for photodynamic therapy, 33,34 illumination of fullerenes dissolved in organic solvents in the presence of oxygen leads to the efficient generation of highly reactive singlet oxygen via energy transfer from the excited triplet state of the fullerene.35 However, some recent reports have shown that in polar solvents, especially those containing reducing agents (such as NADH at concentrations found in cells), illumination of various fullerenes will generate different reactive oxygen derivatives, such as superoxide anion. 36 These two pathways (singlet oxygen and superoxide anion) are analogous to the Type II and Type I photochemical mechanisms frequently discussed in PDT with tetrapyrroles. 37 , 38 Fullerenes with their triply degenerate, low lying LUMO are excellent electron acceptors capable of accepting as many as six electrons.…”
Section: Photochemical Mechanismsmentioning
confidence: 89%
“…Yamakoshi et al 36 carried out a photochemical study comparing energy transfer processes (singlet oxygen 1 O 2 ) and electron transfer (reduced active oxygen radicals such as superoxide anion radical O 2 −• ), using various scavengers of ROS, physicochemical (electron paramagnetic resonance (EPR) radical trapping and near-infrared spectrometry), and chemical methods (nitro blue tetrazolium reaction with superoxide). Whereas 1 O 2 was generated effectively by photoexcited C 60 in nonpolar solvents such as benzene and benzonitrile, they found that O 2 −• and OH • were produced instead of 1 Highly water-soluble hexa(sulfobutyl)fullerenes (FC4S) were synthesized by the treatment of C 60 in dimethoxyethane with sodium naphthalide followed by reacting the resulting hexaanionic fullerene intermediates with an excess of 1,4-butanesulfone.…”
Section: Photochemical Mechanismsmentioning
confidence: 99%
“…The CL signals were not evidently changed, even when scavengers at a high concentration (0.05 mol/L DABCO or tryptophan) were added to the system of MCLA on CaO 2 (Fig. 3) (31,32). This method was also chosen for these experiements.…”
Section: Confirmation Of Ros On Cao 2 By CLmentioning
confidence: 99%
“…Photoexcitation of fullerene derivatives efficiently produces an excited triplet state (Arbogast et al, 1991;Guldi and Prato, 2000) and through energy and electron transfer to molecular oxygen produce both singlet molecular oxygen (Prat et al, 1999) and superoxide (Yamakoshi et al, 2003). Although the carboxylated water-soluble fullerene derivatives were not found to be phototoxic to B lymphocytes (Irie et al, 1996), the malonic acid derivatives of fullerenes were found to be cytotoxic and phototoxic to both HeLa (Yang et al, 2002) and Jurkat cells (Rancan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%